Color At the artist Fayek Hassan: اخلاص ياس خضير (Al-Academy, 2015)
The shift that caused the fading art schools and the brightness of the other, which dictate the work of art based surface and defect lasting regeneration led the researcher to stop at the color of his study, as an element of fixed and mobile at the same time, hard as a lieutenant of the painting plastic and brick construction that supports a painting, The variable that follows the doctrine of the artist and the philosophy of the community, because of the extrapolation of his biography, especially in modern art and beyond is clear that compose a variety of ways and so as to ensure continuity vital to the process of drawing, color in all modes is responsible for editing shapes on the surface imaging is, without a line, shape and dimensions of imaginary and real enjoy the entity physical coherent Mtat of disclosure form outer material for its content very clearly to the point that he became in modern art the key element that is ahead of configuration items Plastic other, has proven that he cannot be considered part of a secondary meaning can marginalize him, the mere contemplation simple works of art and even of things natural around us confirms that he fixed part cannot be separated or canceled, it is the cover of phenomena and shapes, and may be the technical infrastructure able to manipulate it and run it, but it does not have a way to put out the equation of aesthetic construction of any structure of art. Was the color for the foundation of painting and cover the surface, and confirms this is a way of dealing with color in various schools and directions of the ages of art, including shares in the detection of Prominent aspects of the aesthetic of color and highlight and emphasize it, until I knew the colors a particular school features aesthetic especially different than in another school The experience of the artist super good associated with the reality and inspired by the cultural heritage in Iraq and ending in living folklore, contemporary and included history of symbolic and that otherwise the fact progress, track experience of color or experience collecting light, it is the first Iraqi artist Velsv color and produced his experiences substantive (values of color) to make it mainly in his paintings. , but the paintings leading on the nature of colors, interdependence and harmony, if perfected the artist's game distribution blocks color perfected the movement in the painting because the color depth and extension, and ripples, and these are all Tgueth gas creativity drawing. Vasloppe loads of privacy, which makes it unique, and away from the similarity of the methods prevailing, albeit within the framework of the modern Iraqi painting in particular.Based on the above Tertsm researcher has specific questions represented a problematic research, namely: What is the pattern or color that the nature of relations Ancoha super good in the filming of the environment. What is similar, is different between the kinds of relations in terms of color